Cannabis linked to improved sleep quality: A preliminary study. (13th April 2021) - Cebrian, J.; Gonzalez-Cuevas, G.
Abstract : Introduction: Sleep disorders are a substantial public health issue with serious consequences on patients' quality of life. Cannabis has been recently suggested as a potential treatment for patients with sleep disorders; however, research on the relationship between cannabis and sleep is still in its infancy. Objectives: The aim of this investigation was to assess whether cannabis use was associated with improved sleep quality. Methods: Our study comprised 173 participants, 42 cannabis users and 131 non-cannabis users, who completed the Pittsburgh Sleep Quality Index (PSQI), the most common self-reported measure of sleep quality. The scale provides a global PSQI score and seven component domain scores, including subjective sleep quality, sleep latency, sleep duration, habitual sleep efficiency, sleep disturbances, use of sleep medication, and daytime functions. Results: Cannabis users self-reported statistically significantly healthier scores than non-cannabis users in the global PSQI as well as the specific domains of subjective sleep quality, sleep latency, as well as sleep disturbances. Conclusions: This preliminary evidence points to the possibility that cannabis could provide effective treatment for patients with sleep disorders. Research into the constituents of cannabis that may have a differential impact on sleep and sleep disorders is warranted.